The Effect of Job Insecurity and Perceived Organizational Inclusion on Outsourcing Employee Performance - Boyas, Jeziano Rizkita (Universitas Nahdlatul Ulama Sidoarjo, 2024)
This study aims to examine the influence of job insecurity and perceived organizational inclusion on the performance of outsourced employees at PT Karya Utama Nusindo (KUN). A quantitative approach was used with a survey method involving 83 respondents from five partners of PT KUN. Job insecurity was measured using 5 indicator items, while Perceived Organizational Inclusion used 6 indicator items. Employee performance uses 6 indicator items. The results showed that job insecurity has a positive and significant effect on employee performance, meaning that job uncertainty actually motivates employees to work better. Meanwhile, perceived organizational inclusion also has a significant positive effect, indicating that an inclusive work environment encourages optimal performance. This research provides insight for companies to leverage these factors in improving outsourced employee performance through a strategic approach that manages job insecurity productively and encourages organizational inclusiveness.